Guru di Era Digital: Pelatihan Implementasi Schoology sebagai Learning Management System bagi Guru SMP Veteran Kota Cirebon - Surya Amami Pramuditya; Cita Dwi Rosita; Siska Firmasari; Sri Asnawati (Universitas Mathla'ul Anwar Banten, 2020)
TEACHERS IN THE DIGITAL ERA: TRAINING ON THE IMPLEMENTATION OF SCHOOLOGY AS A LEARNING MANAGEMENT SYSTEM FOR TEACHERS OF SMP VETERAN CIREBON CITY. Distance education is a natural learning system that involves two-way communication through the media between educators and students when there is a distance that separates them. To integrate the two-way communication process requires a learning management system (Learning Management System). One of the LMS platforms is Schoology. Schoology allows users to create, manage, and interact with each other and share academic content. Schoology provides solutions for teachers to improve their professionalism in the digital age, especially in the use of technology for learning. The resource person trains participants with the lecture method, which explains how to use the menus and tools contained in LMS Schoology, as well as simulations of how to implement them in learning. The training stage consists of the preparation phase and the implementation phase of the training. The target of the training is the teachers of all subjects in Cirebon Veterans Junior High School. Indicators of training implementation with evaluation during the training process and post-training evaluation. From the results of the community service activities, during the face-to-face events, the teachers looked enthusiastic, only when the exercises were online (non-face-to-face), only one teacher actively participated out of a total of 9 teachers who became training participants. Based on observations, few teachers took part in online activities because of their busy operations in classroom teaching, which had to pursue productive weeks of learning.